2021
DOI: 10.1021/acscatal.1c00435
|View full text |Cite
|
Sign up to set email alerts
|

Highly Dispersed Sn-beta Zeolites as Active Catalysts for Baeyer–Villiger Oxidation: The Role of Mobile, In Situ Sn(II)O Species in Solid-State Stannation

Abstract: Solid-state incorporation of Sn into beta (β) zeolites is a fast and efficient method to obtain Lewis acidic Snβ catalysts with high activity. The present work emphasizes the fundamental role of the heat-treatment atmosphere in the solidstate incorporation of active Sn in zeolites. Via an array of characterization tools including N 2 -physisorption, X-ray diffraction, diffuse reflectance UV−vis spectrocopy, Fourier transform infrared spectroscopy, X-ray photoelectron spectroscopy, and 119 Sn Mossbauer spectros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
59
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 41 publications
(67 citation statements)
references
References 97 publications
8
59
0
Order By: Relevance
“…However, in literature it is reported that SnO2 as precursor gives inactive Snβ catalysts containing high amount of SnO2 clusters. 8,37 Figure 3 shows that untreated 5SnO2 deAlβ indeed did not possess any catalytic activity, which is in agreement with literature. After the reduction-reoxidation cycle, the 5SnO2 deAlβ samples reaches 63 mMCL• h -1 , exceeding the 5Snβ-air catalyst made with Sn(II) acetate and supporting our hypothesis.…”
Section: Baeyer-villiger Oxidation (Bvo) Reactionsupporting
confidence: 89%
See 4 more Smart Citations
“…However, in literature it is reported that SnO2 as precursor gives inactive Snβ catalysts containing high amount of SnO2 clusters. 8,37 Figure 3 shows that untreated 5SnO2 deAlβ indeed did not possess any catalytic activity, which is in agreement with literature. After the reduction-reoxidation cycle, the 5SnO2 deAlβ samples reaches 63 mMCL• h -1 , exceeding the 5Snβ-air catalyst made with Sn(II) acetate and supporting our hypothesis.…”
Section: Baeyer-villiger Oxidation (Bvo) Reactionsupporting
confidence: 89%
“…The Ea values of the MPV and BVO reaction are comparable to the one reported for HT Snβ (63 kJ•mol -1 ), 33 and BVO PS SS Snβ (70 kJ•mol -1 ) 8 , respectively. Moreover, these Ea-values indicate that all reactions were performed in absence of mass transfer limitations.…”
Section: Kinetic Catalysts Parameters For Bvo and Mpv Reactionssupporting
confidence: 84%
See 3 more Smart Citations